KARAKALPAK FOLKLORE AND ISSUES OF TRANSLATION - Rzaeva, R.K.; Eshimbetova, N.M. (FAN va JAMIYAT, 2016)
The article deals with the study of Karakalpak folklore and issues of literary translation. The publication of "Karakalpak folklore" in 100 volumes and holding an international conference in connection with it is a very important event not only for our country but for all peoples of Central Asia. Folklore is one of the valuable sources of education and effective means in the spiritual-moral upbringing of young generation. The translation of the best works of folklore from Karakalpak into English is one of the actual issues today, it gives wide opportunities to the people of other countries to get acquainted with the culture and national heritage of our country.